Клучни фактори и влијанија на колаборативни модели за перформансите на е-владини услуги - Реџепи, Артан (ФИНКИ, УКИМ, Скопје, 2019)
Most of local government institutions declare that they recognize the roles of ICT and how they can be utilized for both services implementations and building relationship with stakeholders and citizens. This allows the adoption of web 2.0 ICT tools as platforms for promoting the public dialogue and participation in decision and policy making. The question raised is to what extent the central and local government institutions understand the functions and roles of ICT and how they should be utilized for both strengthening the public administration institution they represent and for building relationship with stakeholders and citizens, which will allow the emergence of the second generation of e-participation. This study analyses the status and provides an initial assessment of e-participation implementation at central and local level in the context of usage social media and alternative forms of collaboration tools in performance and post acceptance of eGovernment information systems. Specifically, this study explores the e-participation implementation from the perspective of usage practices of such communication platforms, and the potential relationship between the online activity of local governments and the citizen engagement. We have argued that the online activity of local governments and key officials is one of the main factors that influence engagement of citizens. This explorative study was conducted from 2014 through 2017 in 38 municipalities, with the broad goal to cover the social media use by local government institutions and key municipal officials. We have examined trends of different set of metrics to obtain relevant dimensions of citizens' reactivity, dialogue engagement in social media platforms of local governments. The analysis has not shown significant correlation between the activity respectively number of posts of local government and the overall engagement level of citizens. In comparison, this paper presents a complementary methodology for increasing youth e-participation in a local government decision making process that is based on a combination of a gamebased learning, citizen co-creation, scenario-based simulation modelling and design thinking. The proposed methodology is illustrated with a case study for the citizen supported efficient design of public spaces in the city of Pristina in Kosovo. The case study elaborates the means to achieve high youth engagement in the decision making process while establishing a non-formal environment for youth training in the topics of energy efficiency, ecology and sustainable public space design. The proposed methodology suggests a new insight into youth e-participation in redesign of public spaces as a valuable input for local government, towards its efforts for providing social, economic and environmental sustainability of public projects. At last, we provide a comparative appraisal of the use of social networks by local level governments versus local government key officials. Implications and importance of those findings are discussed.
Key factors and impacts of collaborative models for performance of e-government services
Докторска дисертација одбранета во 2019 година на Факултетот за информатички науки и компјутерско инженерство во Скопје, под менторство на проф. д–р Владимир Трајковиќ.
Keywords: e-government, e-participation, social networks metrics, evaluation of e-government services, sustainability development, youth engagement